PARTISIPASI MASYARAKAT DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA LEMOH TIMUR KECAMATAN TOMBARIRI TIMUR KABUPATEN MINAHASA - Lenak, Christin Novita; Rares, Joyce Jacinta; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACK : To realize the goal of national development, the government is giving great attention to the development in the countryside. To the need to increase the participation of rural communities, as a form of cooperation between the government and the community in building a region (especially rural areas). By utilizing the Village Fund Allocation (ADD), the village could play a more active in mobilizing community development. The issue is still low community participation in village activities financed from the Village Fund Allocation. This was due to the lack of socialization and communication of government and society. The purpose of this study is to provide an overview of community participation in the management of the Village Fund Allocation (ADD) in the village of East Lemoh District of East Tombariri. This study used a qualitative approach, with a view to obtaining an overview of community participation in the management of the Village Fund Allocation. Data collection techniques in this study by observation, interviews, and documentation. The Results showed that public participation in the management of the Village Fund Allocation is still not optimal because the public just so much involved in implementation, lack of awareness about existing Village Fund Allocation. Public awareness is still lacking to participate also caused because of lack of socialization of the government on the allocation of village funds. Thefore the suggestion of this research, rural government should always socialize the Village Fund Allocation Policy (ADD) to the public so that the public could understand the policy. Keywords: Public Participation, Management, Village Fund Allocation.